Control the Speed of Separately Excited Dc Motor Using Sliding Mode Controller - Chinedu James Ujam; Adebayo Adeniyi D. (Engineering And Technology Journal, 2024)
This study looks into how a Sliding Mode Controller (SMC) can be used to control a Separately Excited DC Motor's (SEDCM) speed. The SMC is utilized to improve the system's resilience to unknowns and disruptions, guaranteeing accurate control under changing operational circumstances. Extensive simulations and experimental settings confirm the suggested control technique, which shows improved performance in terms of stability, disturbance rejection, and speed tracking. The results further the development of DC motor control techniques, especially in situations where robustness and precision are crucial.